The impact of stress and anesthesia on animal models of infectious disease - Layton, Rachel; Layton, Daniel; Beggs, David; Fisher, Andrew; Mansell, Peter; Stanger, Kelly J. (Frontiers in Veterinary Science, 2023)
Stress and general anesthesia have an impact on the functional response of the organism due to the detrimental effects on cardiovascular, immunological and metabolic function, which could limit the organism's response to an infectious event. Animal studies have formed an essential step in understanding and mitigating infectious diseases, as the complexities of physiology and immunity cannot yet be replicated in vivo. Using animals in research continues to come under increasing societal scrutiny, and it is therefore crucial that the welfare of animals used in disease research is optimised to meet both societal expectations and improve scientific outcomes. Everyday management and procedures in animal studies are known to cause stress, which can not only cause poorer welfare outcomes, but also introduces variables in disease studies. Whilst general anaesthesia is necessary at times to reduce stress and enhance animal welfare in disease research, evidence of physiological and immunological disruption caused by general anaesthesia is increasing. To better understand and quantify the effects of stress and anaesthesia on disease study and welfare outcomes, utilising the most appropriate animal monitoring strategies is imperative. This article aims to analyse recent scientific evidence about the impact of stress and anesthesia on uncontrolled variables, as well as monitoring strategies and technologies in animal models during infectious diseases.